Living standards, poverty and inequality in the UK: 2017/2018 to 2021/2022 - Andrew Hood; Tom Waters (Institute for Fiscal Studies (IFS), 2017)
Debates over living standards, poverty and inequality in the UK are often hampered by the fact that official data on household incomes are available only with a significant lag. Currently, the latest statistics are for 2015-16. In this report, we attempt to fill this gap by estimating what has happened since 2015-16 to household incomes and poverty rates. We also look at how they might evolve up to 2021-22 if current tax and benefit policy plans are kept to and if the macroeconomic forecasts from the Office for Budget Responsibility (OBR) - for things such as earnings and employment - were correct.
Keywords: 330